EFFECT OF CO-BRANDING, BRAND IMAGE, AND SOCIAL MEDIA MARKETING ON GEN Z PURCHASE INTENTION IN DENPASAR - Cananda, Diva Paramita; Ratih Nurmalasari, Ni Made (Sekolah tinggi ilmu ekonomi pemuda, 2025)
This study aims to determine the effect of co-branding, brand image, and social media marketing on the purchase intention of Gen Z consumers toward the Le Minerale × Indonesian National Football Team collaboration product in Denpasar City. The collaboration between Le Minerale and the national team represents an innovative marketing strategy that appeals to young consumers who are highly engaged on social media and value strong brand identity. This research employs a quantitative method with multiple linear regression analysis. Data were collected through questionnaires distributed to 114 Gen Z respondents in Denpasar who were aware of or had purchased the collaboration product. The results indicate that co-branding has a positive and significant effect on purchase intention, with a t-value of 3.816 and a significance level of 0.000. Brand image also shows a positive and significant effect, with a t-value of 2.540 and a significance level of 0.000, while social media marketing demonstrates a positive and significant influence, with a t-value of 4.200 and a significance level of 0.000. Simultaneously, these three variables significantly affect purchase intention, as shown by an F-value of 41.691 and a significance level of 0.000. The Adjusted R² value of 0.519 indicates that 51.9% of the variation in purchase intention is explained by these variables. These findings suggest that a stronger co-branding strategy, a positive brand image, and effective social media marketing can enhance Gen Z’s purchase intention toward the Le Minerale × Indonesian National Team product in Denpasar City. Keywords: Co-Branding, Brand Image, Social Media Marketing, Purchase Intention